Does trade with multinationals induce greener production? Evidence from the Bangladesh fashion industry - Iqbal, Kazi; Mahzab, Moogdho; Motohashi, Kazuki; Takayama, Haruka (International Growth Centre, 2025)
This working paper examines the impact of trading with global fashion brands on the environmental performance of suppliers in Bangladesh. The study finds that an increase in the number of exporters to brand multinationals improves the river water quality surrounding these exporters, highlighting the crucial role multinational buyers play in mitigating industrial pollution.